ANALISIS PSAK NO 109 TERHADAP PELAPORAN KEUANGAN AKUNTANSI ZAKAT, INFAK DAN SEDEKAH PADA BAZNAS PROVINSI JAWA BARAT - Yuni Fitria Agung; Nunung Nurhayati; Sri Fadilah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to determine whether the accounting treatment for zakat, infaq and alms in West Java Province BAZNAS is in accordance with PSKA No. PSAK No. 109 concerning zakat accounting. The method used is a descriptive approach and the type of data used is qualitative. The results of this study conclude that BAZNAS West Java Province has implemented the use of PSAK No. 109 concerning zakat, infaq and alms accounting which aims to regulate the recognition, measurement, presentation and disclosure of zakat, infaq and alms transactions.